Synergistic effect of regorafenib with aminoglycosides in ferroptosis-mediated liver injury - Raja Dahar, Maha; Zhou, Shaojun; Hu, Haihong; Lei, Jinxiu; Zeng, Kui; Yu, Lushan (Frontiers in Pharmacology, 2025)
BackgroundCombination therapy of anticancer drugs with antibacterial agents has numerous advantages, but these may develop adverse drug events that were rarely studied. Specifically, regorafenib (REGO) mediates ferroptosis and causes liver injury when used in combination with aminoglycosides (AGs); however, this interaction remains unexplored.MethodologyThe study was conducted using both in vivo and in vitro assays involving Sprague–Dawley (SD) rats and HepG2/Huh7 to investigate ferroptosis-associated liver injury. The drugs REGO, amikacin (AMK), and gentamicin (GNT) were administered individually as well as in combination to evaluate their noxious effects on the liver. Subsequently, biochemical, histological, and transcriptomic analyses were carried out, and protein expressions were investigated using the immunoblotting assay to explore the mechanisms underlying ferroptotic-mediated liver injury.ResultsThe findings of the in vivo assay revealed that the combination therapy of regorafenib with aminoglycosides augments alanine transaminase (180%–200%), aspartate aminotransferase (120%–140%), malondialdehyde, and Fe2+ levels. It decreases the level of antioxidants and alters histomorphology in SD rats compared to individual therapy. The in vitro assay results validate the enhanced levels of cellular iron, lipid peroxidation, reactive oxygen species, and lactate dehydrogenase release, indicating enhanced toxicity. In contrast, it decreased the cell viability ratio, glutathione level, and integrity of the mitochondrial membrane. The real-time quantitative polymerase chain reaction (RT-qPCR) and immunoblotting assay results show downregulation of GPX4 and SLC7A11 expressions, along with elevation of ALOX-15 (3- to 6-fold change).ConclusionThus, combination therapy of regorafenib with amikacin and gentamycin causes significant elevation of iron and lipid peroxidation levels and alteration in protein expressions, which mediates ferroptotic cell death and leads to liver injury.